PENGARUH KUALITAS MAKANAN DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA ANGKRINGAN 88 KOTA DEPOK - Lukman Fauzi; Mahnun Mas’adi (Jurnal Manajemen & Pendidikan [JUMANDIK], 2026)
The purpose of this study was to determine the effect of food quality and service quality on customer satisfaction at Angkringan 88, Depok City. The method used was quantitative. The sampling technique used the Slovin formula and obtained a sample of 95 respondents. Data analysis used validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients, and hypothesis tests. The population in this study were consumers at Angkringan 88, Depok City, and the number of saturated samples was 95 respondents. Data collection methods used questionnaires with a Likert scale, observation, and literature studies. The results of this study indicate that food quality significantly influences customer satisfaction, with a coefficient of determination of 49.4%, and the hypothesis test obtained t count > t table or (9.522 > 1.986). Service quality significantly influences customer satisfaction, with a coefficient of determination of 56.4%, and the hypothesis test obtained t count > t table or (10.974 > 1.986). Food quality and service quality simultaneously significantly influence customer satisfaction, with the regression equation Y = 17.836 + 0.372X1 + 0.478X2, with a coefficient of determination of 63.0%, while the remaining 37.0% is influenced by other factors. The hypothesis test obtained F count > F table or (12.761 > 9.10).